The Sanctuaries for Witch-hunt Victims in Northern Ghana - Felix Riedel (Modern Africa, 2018)
Witch-hunts in Ghana’s Northern Region occur mainly among neighbours and members of the extended family. Triggers for accusations are disease, death and accidents. With many exceptions, the accused are postmenopausal women. Accusers include children, women and men alike. Witch-hunts do only ocassionally target specific behaviour or deviancy: they are registered as accidental and “unjust” by almost all victims. Most accusations disrupted productive relationship and reaped no benefit for the accusers. Victims are often tortured to produce confessions. The accusers rely on dreams for singling out the accused, while the latter are then forced to chicken- and potion-ordeals at diverse shrines to determine their guilt or innocence. Exorcisms include potions and shaving. Today, about 800 victims of witchcraft-accusations live in nine sanctuaries for witchhunt-victims to dodge further accusations and lynchings. While diverse in character, eight of the nine sanctuaries adhere to an earth-shrine-complex typical for Northern Ghana and beyond. Social work with the victims and educational campaigns by NGO’s are well-tried and promising, but governmental malpractice and media attention have reaped mixed results so far.